Income inequality and economic complexity in Africa: the moderating role of governance quality - Amsalu Bedemo Beyene (Cogent Social Sciences, 2024)
This study examines the relationship between economic complexity and income inequality in 24 selected African countries. Specifically, it investigates the moderating role of governance quality in the link between income inequality and economic complexity. The study applied the systems GMM panel estimation method to data spanning from 2000 to 2018, sourced from the World Bank, Harvard Dataverse, and Baker Library databases. The findings indicate that economic complexity significantly worsens income distribution in the study area. However, when the composite governance indicator is used as a moderator, the coefficient of the interaction term becomes negative and significant, implying that governance factors play a crucial role in mitigating the adverse effects of economic complexity on income inequality. Similar results were arrived in the disaggregated analysis of governance quality indicators, where each governance factor offsets the negative impact of complexity on income inequality. The findings suggest policy measures aimed at enhancing the quality of governance system to counteract the deteriorating effects of economic complexity on income inequality.